A highly pH-sensitive nanowire field-effect transistor based on silicon on insulator - Presnov, Denis E.; Amitonov, Sergey V.; Krutitskii, Pavel A.; Kolybasova, Valentina V.; Devyatov, Igor A.; Krupenin, Vladimir A.; Soloviev, Igor I. (Beilstein Journal of Nanotechnology, 2013)
Background: An experimental and theoretical study of a silicon-nanowire field-effect transistor made of silicon on insulator by CMOS-compatible methods is presented.Results: A maximum Nernstian sensitivity to pH change of 59 mV/pH was obtained experimentally. The maximum charge sensitivity of the sensor was estimated to be on the order of a thousandth of the electron charge in subthreshold mode.Conclusion: The sensitivity obtained for our sensor built in the CMOS-compatible top-down approach does not yield to the one of sensors built in bottom-up approaches. This provides a good background for the development of CMOS-compatible probes with primary signal processing on-chip.
Keywords: charge/field sensor; field-effect transistor; nanowire; pH sensor; silicon-on-insulator